Exploring education for sustainable development (ESD) approaches among technical and vocational education and training (TVET) teachers - Rosman, Rabbiatul Natrah; Omar, Muhd Khaizer (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Teachers are accountable to disseminate knowledge on Education for Sustainable Development (ESD) to the public society, particularly in schools. ESD refers to a holistic pedagogy approach which empower students to have awareness and contribute to a better environment, society and economy. It is important for Technical and Vocational Education and Training (TVET) teachers to have a deep understanding on ESD concept and element, specifically in teaching approaches throughout student’s learning process. TVET teachers are also explicitly positioned as the agents of change, which required them to comprehend the knowledge and concept of ESD in order to ensure an effective approach for students. Thus, teachers need to have the competency, commitment and motivation not only as person that contribute on imparting knowledge, but also to empower the sustainable qualities within the students. What knowledge and skills should teachers obtain in order to practice ESD in the classroom and teaching approaches? The aim of this study is to explore the ESD approaches among TVET teachers through teachers’ perceptions and views that related to acquisition of knowledge, competency and instructional strategy as well as motivation in the direction of fostering ESD amongst students.